ChemInform Abstract: α‐Ketophosphonates as Ester Surrogates: Isothiourea‐Catalyzed Asymmetric Diester and Lactone Synthesis. Issue 45 (23rd October 2014) - Smith, Siobhan R.; Leckie, Stuart M.; Holmes, Reuben; Douglas, James; Fallan, Charlene; Shapland, Peter; Pryde, David; Slawin, Alexandra M. Z.; Smith, Andrew D.
Abstract The reaction can be scaled up.